Delayed diagnosis in a house of correction: Smith–Magenis syndrome due to a de novo nonsense RAI1 variant. Issue 9 (17th June 2016) - Yeetong, Patra; Vilboux, Thierry; Ciccone, Carla; Boulier, Kristin; Schnur, Rhonda E.; Gahl, William A.; Huizing, Marjan; Laje, Gonzalo; Smith, Ann C. M.
Abstract : We report a 25‐year‐old female confirmed to have Smith–Magenis syndrome (SMS) due to a de novo RAI1 variant. Her past history is significant for developmental and intellectual delay, early and escalating maladaptive behaviors, and features consistent with significant sleep disturbance, the etiology of which was not confirmed for over two decades. The diagnosis of SMS was initially suspected in 1998 (at age 12 years), but that was 5 years before the initial report of RAI1 variants as causative of the SMS phenotype; cytogenetic fluorescence in situ hybridization studies failed to confirm an interstitial deletion of 17p11.2. Re‐evaluation for suspected SMS was pursued with RAI1 sequencing analysis in response to urgent parental concerns of escalating behaviors and aggression with subsequent incarceration of the subject for assault of a health professional. Genetic analysis revealed a de novo RAI1 (NM_030665.3) nonsense variant, c.5536C>T; p.Q1846X. This case illustrates the importance of confirming the SMS diagnosis, which is associated with cognitive and functional impairment, as well as significant psychiatric co‐morbidities and behavioral problems. The diagnosis was particularly relevant to the legal discussion and determination of her competence to stand trial. As other similar cases may exist, this report will help to increase awareness of the possibility of a very late diagnosis of SMS, with the need for re‐evaluation of individuals suspected to have SMS who were initially evaluated prior to the identification of the RAI1 gene. © 2016 Wiley Periodicals, Inc.